The Interleukin-1α Precursor is Biologically Active and is Likely a Key Alarmin in the IL-1 Family of Cytokines - Kim, Busun; Lee, Youngmin; Kim, Eunsom; Kwak, Areum; Ryoo, Soyoon; Bae, Seunghyeon; Azam, Tania; Kim, Soohyun; Dinarello, Charles A. (Frontiers in Immunology, 2013)
Among the eleven members of the IL-1 family cytokines, the precursors of IL-1a, IL-1b, and IL-33 have relatively long N-terminal pro-sequences of approximately one hundred amino acid residues prior to the N-terminus of the mature forms. Compared to the mature forms secreted from the cell, 80-90% of the primary translation product is in the intracellular compartment in the precursor form. However, the precursors are readily released from cells during infections but also with non-infectious conditions such a hypoxia and trauma. In this setting, the precursors act rapidly as “alarmins” in the absence of a processing mechanism to remove the pro-sequence and generate a mature form. In the case of IL-1a, the release of the precursor activates adjacent cells via receptor-mediated signaling. However, there are no data comparing the specific activity of the IL-1a precursor to the mature form. In the present study, we compared the precursor and mature forms of recombinant human IL-1a, IL-1b and IL-33 proteins on the induction of cytokines from A549 cells as well as from human peripheral blood mononuclear cells (PBMC). Similar to the mature form, the IL-1a precursor was active in inducing IL 6 and TNFa, whereas the precursor forms of IL 1b and IL-33 were not active. On PBMC, precursor and mature IL-1a at 0.04 and 0.2 nano-mole were equally active in inducing IL-6. Given the fact that during necrotic cell death, the IL-1a precursor is released intact and triggers IL-1 receptors on tissue macrophages, these data identify the precursor form of IL-1a as a key player in sterile inflammation.